Does Anger Expression Help or Harm Leader Effectiveness? The Role of Competence-based versus Integrity-based Violations and Abusive Supervision - Wang, Lu; Restubog, Simon; Shao, Bo; Lu, Vinh; Van Kleef, Gerben A. (Academy of Management Journal, 2018)
The question of how leaders’ expressions of anger influence their effectiveness has long intrigued researchers and practitioners. Drawing on emotions as social information theory, we suggest the effects of leaders’ expressions of anger depend on both the type of violation about which anger is expressed and the type of leader who expresses it. We test this in a series of studies using experimental and field methods. Study 1 shows that a leader’s anger expression in response to followers’ integrity-based violations enhances observers’ perceptions of leader effectiveness, whereas anger in response to followers’ competence-based violations diminishes observers’ perceptions of leader effectiveness. Study 2 shows that these divergent effects occur because anger in response to integrity-based violations elicits beneficial inferential reactions among followers who observed the anger, whereas anger in response to competence-based violations provokes harmful affective reactions. Study 3 demonstrates that the negative effects of anger expressed toward competence-based violations are exacerbated, and positive effects of anger expressed toward integrity-based violations weakened, when a leader is perceived as abusive. These findings help reconcile divergent perspectives on the effects of leader anger expression, suggesting that anger can enhance perceived leader effectiveness when expressed in the right situation and by the right person.